USING OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN TEACHING PHYSICS OF STUDENTS NONPHYSICAL SPECIALTIES OF PEDAGOGICAL HIGHER EDUCATIONAL ESTABLISHMENT - Salnyk, І.В. (Journal of Information Technologies in Education (ITE), 2013)
The problems that arise in learning physics of students nonphysical specialties associated with the lack of motivation in them to occupations that cause low levels of learning. One way of solving the problem is the integrated use of ICT in the learning process in higher education. In the course of physical workshop ICT can solve the problems associated with low experimental preparing students of nonphysical specialties.